1998
DOI: 10.1111/j.1545-5300.1998.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of African American Families in Research on Chronic Illness: A Multisystem Recruitment Approach

Abstract: Our multisystem approach addressed the recruitment of African American families with a chronically, physically ill member. The approach focused on the social transactions between the family, the healthcare team, and the research staff, and the influence of these transactions on family recruitment. This multisystem approach included three core strategies: defining the membership of families in a culturally appropriate fashion and engaging those members; engaging the healthcare team; and building and maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Therefore, for the purpose of this report, family dynamics are regarded as the ongoing interpersonal interactions and relationships between family members (i.e., siblings and parents) that influence decisions regarding enrollment. 8,9 The concept of integrating the CAA into regimens used in GFS resulted from performing several ethnographic studies. 10,11 Previously, we conducted in-depth, semistructured interviews of open-ended questions with DN patients and their relatives (a subset of FIND participants) to explore their health beliefs about T2DM and DN and the associated ethical issues toward participation in GFS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for the purpose of this report, family dynamics are regarded as the ongoing interpersonal interactions and relationships between family members (i.e., siblings and parents) that influence decisions regarding enrollment. 8,9 The concept of integrating the CAA into regimens used in GFS resulted from performing several ethnographic studies. 10,11 Previously, we conducted in-depth, semistructured interviews of open-ended questions with DN patients and their relatives (a subset of FIND participants) to explore their health beliefs about T2DM and DN and the associated ethical issues toward participation in GFS.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis: This case is representative of at least one third of the probands interviewed during previously conducted ethnographic studies. 8,9 After numerous attempts to recruit her family, the patient revealed that she had little interaction with her siblings. By identifying and excluding this subset of probands, recruiters optimize their efforts by enrolling families as opposed to willing probands with unwilling relatives.…”
Section: Contextual Assessment Approachmentioning
confidence: 99%
“…We listen respectfully to patients' reports of symptoms and talk about possible treatments, or no treatment when none is available. We try to engage a family member and feed back information when the patient seems to be non-compliant by physical parameters (91,92). Brock (93) found that knowledge was negatively correlated to uncertainty; level of education was positively correlated with coping effectiveness.…”
Section: Compliancementioning
confidence: 98%
“…Rather than hiring only people with strong clinical or science backgrounds, Abshire et al 32,35 argue that a best practice for staffing longitudinal clinical research projects includes hiring staff with strong communication skills and knowledge of local communities. In addition to interpersonal skills for recruitment, other commonly cited qualities and skills include empathy, 44 which impacts how recruiters relate to participants; group communication competencies, including effective conflict resolution and consensus-building; 45 and the ability to work with interdisciplinary team members by focusing on (or training to improve) building shared meanings. 46 Through all of the interviews, we heard that the AoURP is not a typical clinical research project.…”
Section: Building and Nurturing Engagement Teamsmentioning
confidence: 99%